2007
DOI: 10.1093/jn/137.6.1375
|View full text |Cite
|
Sign up to set email alerts
|

Avenanthramides Are Bioavailable and Have Antioxidant Activity in Humans after Acute Consumption of an Enriched Mixture from Oats

Abstract: The consumption of polyphenols is associated with a decreased risk of cardiovascular disease. Avenanthramides (AV), alkaloids occurring only in oats, may have anti-atherosclerotic activity, but there is no information concerning their bioavailability and bioactivity in humans. We characterized the pharmacokinetics and antioxidant action of avenanthramide A, B, and C in healthy older adults in a randomized, placebo-controlled, 3-way crossover trial with 1-wk washout periods. Six free-living subjects (3 mol/L, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
171
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(182 citation statements)
references
References 53 publications
7
171
3
1
Order By: Relevance
“…However, we did not find the same effect after the 8 week CEB consumption. These results are consistent with a temporal effect of polyphenols on elevated GSH concentrations reported by Chen et al [37]. In addition to GSH:GSSG ratio, we noted that SOD activity but not GPx was greater after chronic CEB consumption.…”
Section: Oxidative Stress and Inflammation Biomarkerssupporting
confidence: 93%
See 1 more Smart Citation
“…However, we did not find the same effect after the 8 week CEB consumption. These results are consistent with a temporal effect of polyphenols on elevated GSH concentrations reported by Chen et al [37]. In addition to GSH:GSSG ratio, we noted that SOD activity but not GPx was greater after chronic CEB consumption.…”
Section: Oxidative Stress and Inflammation Biomarkerssupporting
confidence: 93%
“…The final anthocyanin concentrations were adjusted with creatinine to account for urine volume differences. Urinary flavanols, flavonols, and phenolic acids were quantified by HPLC with electrochemical detection [31,37]. Concentrations of individual polyphenols were determined using calibration curves constructed with authenticated standards.…”
Section: Polyphenol Bioavailabilitymentioning
confidence: 99%
“…It is well known that SOD serves as the first gatekeeper in the antioxidant defense system designed to scavenge superoxide anions (Reiter et al, 2000), while GSH-Px is a catalyzer that activates the reaction of lipid hydroperoxides with reduced glutathione to form glutathione disulfide (Venukumar and Latha, 2002). An avenanthramides (AVE)-enriched mixture extracted from oat was reported to increase human plasma GSH-Px activity by 30%-35% (Chen et al, 2007). In this study, both SOD and GSH-Px activities were significantly downregulated in H 2 O 2 -treated groups.…”
Section: Oatp Intervention In H 2 O 2 -Induced Fibroblast Damage Withmentioning
confidence: 61%
“…Both animal studies and human clinical trials confirmed that oats antioxidants have the potential of reducing cardiovascular risks by lowering serum cholesterol, inhibiting LDL cholesterol oxidation and peroxidation (Cook & Samman 1996;Ji et al 2003;Inglett & Chen 2012). Therefore, it is emphasised that the consumption of oats and oats products is extremely important to reduce the risk of cardiovascular disease (Bazzano et al 2003;Chen et al 2004Chen et al , 2007Singh et al 2013). Another study has indicated that the consumption of oats and oats bran may reduce the risk of colon cancer not only because of their high fiber contents but also due to AVAs (Guo et al 2010).…”
Section: Effects Of Avenanthramides On Healthmentioning
confidence: 99%